IMPLEMENTATION OF “SANGA MANDALA” CONCEPT IN PATIRTAN WATUGEDE - SINGOSARI (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Patirtan Watugede is the royal heritage site of Singhasari, in the form of a bathing pool. Singhasari Kingdom is an ancient kingdom, centered in the region of Malang, which adheres to the Shiva-Buddhist belief. The concept of Sanga Mandala is a spatial orientation arrangement, derived from Shiva-Buddhist beliefs. In the Sanga Mandala concept, the cosmological orientation of space has a hierarchy based on its function. The concept of Sanga Mandala, is a combination of North-South and East-West orientations. North is believed to be a high place is the main. South as a symbol of the sea, a low place, is bad. Orientation of the East is the main, while the West is bad. A study of spatial patterns at the Patirtan Watugede site was carried out descriptively which was ideographical. This study aims to describe the meaning of the Patirtan Watugede spatial layout, based on the Sanga Mandala concept. The meaning of spatial orientation, obtained by analyzing ancient map documents, field observations and historical information. As a result of the research findings, there is the concept of Sanga Mandala in the orientation of Patirtan Watugede. The holy water source area, as the most sacred place, is in the Northeast.